Adsorption of Lead and Copper Using Water Hyacinth Compost (Eichornia Crassipes) - Kiky Frederika Rumapar; Barlah Rumhayati; Rachmat Triandi Tjahjanto (The Journal of Pure and Applied Chemistry Research, 2014)
Adsorption ofheavy metals Pb and Custudies have been carried out usinga compost of plant water hyacinth (Eichornia crassipes). First steps of the compostingis fermenting fresh hyacinth plants that have been enumeratedwithmolasses and water. Once formed, the compost is used as an adsorbent for the adsorption of heavy metals Pb and Cu. After that process, the water hyacinth compost have been characterized to determine the humic acid content, as well as the functional group content of heavy metals Pb and Cu. Determination of general conditions on the adsorption of Pb and Cu performed with adsorbent mass variations, variations in pH and the concentration variation and studying adsorption isotherm. The results showed that the adsorption of Pb in optimum condition occurs in adsorbentmass of 1.2 g with pH 5. As for the adsorption of Cu on the optimum conditions occur in the adsorbent mass of 0.8 g at pH 6. Results also able to adsorb up to 95.13% Pb andup to 91.42% Cu. Pb and Cu adsorption using adsorbents of water hyacinth compost more models to follow Langmuir than Freundlich models.